A facile synthesis of CeO2 from the GO@Ce-MOF precursor and its efficient performance in the oxygen evolution reaction - Ahmed Malik, Wasif Mahmood; Afaq, Sheereen; Mahmood, Azhar; Niu, Li; Yousaf ur Rehman, Muhammad; Ibrahim, Muhammad; Mohyuddin, Abrar; Qureshi, Ashfaq Mahmood; Ashiq, Muhammad Naeem; Chughtai, Adeel Hussain (Frontiers in Chemistry, 2022)
Electrochemical water splitting has enticed fascinating consideration as a key conduit for the advancement of renewable energy systems. Fabricating adequate electrocatalysts for water splitting is fervently preferred to curtail their overpotentials and hasten practical utilizations. In this work, a series of Ce-MOF, GO@Ce-MOF, Calcinated Ce-MOF and Calcinated GO@Ce-MOF were synthesized and used as high proficient electrocatalysts for oxygen evolution reaction. The physic-chemical characteristics of the prepared samples were measured by diverse analytical techniques including SEM, HRTEM, FTIR, BET, XPS, XRD and EDX. All materials underwent Cyclic Voltammetry tests and evaluated by Electrochemical Impedance Spectroscopy and Oxygen Evolution Reaction. Ce-MOF, GO@Ce-MOF, Calcinated Ce-MOF and Calcinated GO@Ce-MOF have remarkable properties, counting enhanced specific surface area, improved catalytic performance in addition to outstanding permanency in the alkaline solution (KOH). These factors upsurge ECSA and intensify the OER performance of the prepared materials. More exposed surface active-sites are present in calcinated GO@Ce- MOF could be the logic for superior electrocatalytic activity. Chronoamperometry of catalyst for 15 hours divulges long-term stability of Ce-MOF during OER reaction. Impedance measurements indicate higher conductivity of synthesized catalysts, facilitating charge transfer reaction during electrochemical water splitting. This study will open up a new itinerary for conspiring highly ordered MOF-based surface active resources for distinct electrochemical energy applications.